Effect of one-week New Zealand blackcurrant extract on rowing performance and cognitive function in national team male rowers - Naderi, A.; Gharaat, M. A.; Berjisian, E.; Willems, M. E. T.; Mojtahedi, S.; Goli, A.; Dehghankar, L.; Koozehchian, M. S. (Research in Sports Medicine, 2025)
This research investigated the impact of New Zealand blackcurrant (NZBC) on 2000-meter rowing ergometer performance and cognitive abilities. Nine trained male rowers from Iran`s national team participated in a double-blind, placebo-controlled crossover study, undergoing three sessions with NZBC (600 mg·day-1), placebo (PL), and control (CL) treatments over seven days, followed by a 14-day washout period. Participants completed a 2000-meter ergometer test provided self-reported ratings of perceived exertion (RPE) and completed a cognitive function assessment five minutes following the rowing exercise. Findings indicated no significant ergogenic benefits from NZBC supplementation (420 ± 12 s) compared to PL (424 ± 15 s) and CL (423 ± 14 s), despite showing a minimal effect size (Cohen`s d = 0.23). Six subjects had negligible enhancements in performance. No changes were seen in cognitive function or RPE (p > 0.05). A seven-day regimen of NZBC did not enhance rowing performance, cognitive function, or RPE.